Racial Discrimination and the Social Contract: Evidence from U.S. Army Enlistment during WWII - Nancy Qian; Marco Tabellini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
This paper documents several new facts about the relationship between discrimination and political exclusion and the motivation to fight in wartime. The Pearl Harbor attack triggered a sharp increase in volunteer enlistment rates of American men, the magnitude of the increase was smaller for Black men than for white men and the Black-white gap was larger in counties with higher levels of racial discrimination. Discrimination reduced the quantity and the quality of Black volunteers. The discouraging effects of discrimination were more pronounced in places that were geographically distant from Pearl Harbor and in states that had joined the Union relatively recently. For Japanese-American men, enlistment rates were higher where the Japanese-American community was not interred than where it was interred. These and other results provide empirical support for the theory that discrimination and political exclusion reduce support for the government when it is under threat.
Keywords: D72; J15; N92; P16; 330; Political and Economic Exclusion; Social Contract; Nation Building